IMPROVING THE STUDENTS’ ABILITY IN TRANSLATING ENGLISH INTO INDONESIAN BASED ON DUFF’S PRINCIPLES - Radiah Hamid; Rati Pujiantri (Universitas Muhammadiyah Makassar, 2013)
This research aimed at finding out the improvement of the students’ ability in translating English into Indonesian especially for Recount text in terms of the meaning and style of the original text. The researcher used a Classroom Action Research (CAR) to explain the improvement, which was conducted in two cycles in which every cycle consisted of four meetings. The location of this research was taken in the second year of Junior High School 2 Sungguminasa with the number of the subject i.e. 36 students. The research findings indicate that the application of Duff’s Principles is significant in improving the students’ translating ability in terms of meaning and style of the original text. It is proved by the mean score of the cycle I is 60.27 then improved to be 72.49 in cycle II. They are higher than the mean score of diagnostic test namely 56.45. It means that there is the improvement of the students’ translating ability in terms of meaning and style of the original text.Keyword: Ability, translating, English, Indonesian, Duff, principle